2021
DOI: 10.1590/1413-81232021265.10702019
|View full text |Cite
|
Sign up to set email alerts
|

Rede de correlações entre qualidade de vida, resiliência e desequilíbrio esforço-recompensa em policiais militares

Abstract: Resumo Objetivo: Analisar a rede de correlações entre as dimensões do Modelo Desequilíbrio Esforço-Recompensa (DER), resiliência e qualidade de vida em policiais militares. Método: Estudo transversal realizado com 258 policiais do Batalhão de Operações Especiais (BOE) da Polícia Militar de uma cidade do Rio Grande do Sul. As escalas do Modelo DER, de resiliência e World Health Quality of Life (WHOQOL-bref) avaliaram o estresse psicossocial, resiliência e qualidade de vida. Foram realizadas estatísticas descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
1
0
5
Order By: Relevance
“…A recent study carried out in Brazil evaluated correlations between the dimensions of the Effort-Reward Imbalance Model, resilience and life quality in military police officers from the Military Police Special Operations Battalion of a city in Rio Grande do Sul. Evaluating resilience, it was found that this construct interferes with life quality, which is another subjective well-being indicator (Tavares, et al [19]). A review study conducted by Brazilian researchers with the aim of evaluating psychological resilience and/or hardiness in military personnel pointed out that the focus of most research is on the correlation between resilience/hardiness and psychosocial aspects and also noted that resilience/hardiness plays a protective role regarding post-traumatic stress disorder (PTSD) (Cotian [20]).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study carried out in Brazil evaluated correlations between the dimensions of the Effort-Reward Imbalance Model, resilience and life quality in military police officers from the Military Police Special Operations Battalion of a city in Rio Grande do Sul. Evaluating resilience, it was found that this construct interferes with life quality, which is another subjective well-being indicator (Tavares, et al [19]). A review study conducted by Brazilian researchers with the aim of evaluating psychological resilience and/or hardiness in military personnel pointed out that the focus of most research is on the correlation between resilience/hardiness and psychosocial aspects and also noted that resilience/hardiness plays a protective role regarding post-traumatic stress disorder (PTSD) (Cotian [20]).…”
Section: Discussionmentioning
confidence: 99%
“…O trabalho em turnos e a dupla jornada de trabalho dificultam o descanso intermitente e o convívio social, agravam o cansaço e a fadiga e interferem na vida familiar 1 . O duplo vínculo laboral interfere na condição física e psíquica do trabalhador, com reflexos negativos no convívio social e na qualidade de vida 19 . Resultados semelhantes foram evidenciados em um estudo com 105 profissionais de enfermagem do norte de Portugal que aponta associação entre a dor musculoesquelética e características individuais e profissionais, como o sexo, o horário de trabalho, a escolaridade, a prática de atividade física, o tempo no emprego e a carga de trabalho 20 .…”
Section: Discussionunclassified
“…Considerada como uma competência que pode ser desenvolvida e aperfeiçoada, envolve uma reconstrução contínua de aspectos pessoais na interação do indivíduo com seu meio, que o capacita e fortalece para o enfrentamento positivo das dificuldades 25 . Como fator de proteção, a resiliência está associada positivamente aos domínios físico e psicológico para a qualidade de vida 19 .…”
Section: Discussionunclassified
“…Teniendo en cuenta el modelo de Lazarus y Folkman (1984), que recalca la capacidad para hacer frente a las demandas, algunas variables como la resiliencia podrían explicar nuestros resultados. De hecho, se han encontrado evidencias de una correlación entre recompensas y resiliencia en una muestra de policías militares brasileños (Tavares, 2015). Haciendo un paralelismo con la dimensión exigencias del modelo DER, podríamos identificar una dimensión de recursos, conformada por las recompensas (extrínseca) y los recursos personales con los que cuenta la persona (intrínseca).…”
Section: Discussionunclassified